2020
DOI: 10.3389/fchem.2020.554732
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Biotin-Tagged Chitosan Oligosaccharides and Assessment of Their Immunomodulatory Activity

Abstract: Chitin, a polymer of β-(1→4)-linked N-acetyl-d-glucosamine, is one of the main polysaccharide components of the fungal cell wall. Its N-deacetylated form, chitosan, is enzymatically produced in the cell wall by chitin deacetylases. It exerts immunomodulative, anti-inflammatory, anti-cancer, anti-bacterial, and anti-fungal activities with various medical applications. To study the immunobiological properties of chitosan oligosaccharides, we synthesized a series of β-(1→4)-linked N-acetyl-d-glucosamine oligomers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 88 publications
1
11
0
Order By: Relevance
“…To increase the applications in biomedical applications, chitosan is transformed into chitosan oligosaccharides, molecules easily soluble in water [ 144 ]. Activities linked to chitosan and chitosan oligosaccharides include antioxidant, antibacterial, anti-HIV, anti-inflammatory, antidiabetic, and immunomodulatory [ 145 ]. In AD, chitosan has a protective effect; it controls the level of amyloid-beta through the expression and activity of the BACE-1 enzyme.…”
Section: Marine Compounds Against Alzheimer’s Disease: From Sea To Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…To increase the applications in biomedical applications, chitosan is transformed into chitosan oligosaccharides, molecules easily soluble in water [ 144 ]. Activities linked to chitosan and chitosan oligosaccharides include antioxidant, antibacterial, anti-HIV, anti-inflammatory, antidiabetic, and immunomodulatory [ 145 ]. In AD, chitosan has a protective effect; it controls the level of amyloid-beta through the expression and activity of the BACE-1 enzyme.…”
Section: Marine Compounds Against Alzheimer’s Disease: From Sea To Cellsmentioning
confidence: 99%
“…The main natural sources of chitin are shrimp and crab shells, which are an abundant byproduct of the food-processing industry and provide large quantities of these polysaccharides to be used in biomedical applications [ 112 ]. They can be also obtained by synthesis [ 145 ]. The extraction of chitin from the shell includes mainly demineralization and deproteinization [ 185 , 186 , 187 ].…”
Section: Isolation Of High-value Molecules With Neuroprotective Effects Against Alzheimer’s Diseasementioning
confidence: 99%
“…Generally, macrophages are crucial to innate cellular immune responses and play a significant role in the phagocyte cell system, which is programmed to identify, engulf, and eliminate apoptotic cells, bacteria, etc. (10,38). The immune system functions to maintain the physiological health of the body and protect it from pathogens through an increased release of inflammatory cytokines (39).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, investigation has also shown that arabinoxylans with immunomodulatory effect could be considered effective bioactive food supplements associated with many health amelioration functions (46). In vitro immunobiological evaluation of chitin-and chitosan-derived oligosaccharides on RAW 264.7 cells obtained results that indicated a beneficial immunomodulation effect referring to the development of cytokine release, phagocytosis, cell proliferation, and respiratory burst (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation